ADSORPTION OF CU(II) AND ZN(II) ON LIQUID WASTE OF ELECTROPLATING HOME INDUSTRY USING SILICA BASED ADSORBENT PREPARED FROM GLASS WASTE - Saputri, Y. P.; Priyambodo, E. (Indonesian Journal of Chemistry and Environment, 2019)
This study aims to (1) knowing the optimum pH and adsorption contact time of Cu(II) and Zn(II) ions in liquid waste of electroplating by silica gel prepared from glass waste, and (2) knowing the adsorption of Cu(II) and Zn(II) ions in liquid waste of electroplating by silica from glass waste. Synthesis of silica gel using sol gel method. In this method, a powder of glass waste is reacted with sodium hydroxide solution to form sodium silicate. Hydrochloric acid solution was added into the sodiumsilicate to form silica gel. Adsorption of Cu(II) and Zn(II) metal ions was done by batch method at various pH and contact time. The experiments shows that  (1) the optimum pH and the optimum contact time for Cu(II) adsorption was 7 and 3 hours, therefore the optimum pH and the optimum contact time for Zn(II) was 8 and 3 hours, (2) the adsorption effectiveness of Cu(II) and Zn(II) in liquid waste of electroplating by silica from glass waste  occurred in pH 7 for 3 hours were 99.9300% and 95.4200%.